Tiktok video as a learning tool in computer keyboarding class/ Milfadzhilah Mohd Jamil and Nashrah Talib - Mohd Jamil, Milfadzhilah; Talib, Nashrah (Universiti Teknologi Mara Selangor, 2022)
The outbreak of Covid-19 changed the culture of learning at all levels of the institution. For two years of Malaysian movement control order (MCO) has urged the students and lecturers to find the media tools to support their learning activities. The study is based on the short videos created from the current social media, TikTok which offers beneficial functions in creating educational videos. TikTok is a social media music video application that use to create and share short videos and music. There are 31 short videos created as support materials in keyboarding class and used by 5 lecturers with 214 students. This paper intents to present some concepts and findings related to the use of TikTok videos as a media for teaching keyboarding in distance learning situations. The finding shows a positive perception toward the use of TikTok in the learning process and contributes positively to the teaching and learning activities.